2017
DOI: 10.1177/0022022117706108
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Parenting Styles and Perceived Child Effortful Control Within Chinese Families in the United States, the United Kingdom, and Taiwan

Abstract: The current study examined the associations between parentally perceived child effortful control (EC) and the parenting styles of 122 Chinese mothers (36 first-generation Chinese immigrants in the United Kingdom, 40 first-generation Chinese immigrants in the United States, and 46 Taiwanese mothers) of 5- to 7-year-old (M age = 5.82 years, SD = .805; 68 boys and 54 girls) children. The findings showed significant cultural group differences in mothers’ reported authoritarian parenting style. Significant associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 75 publications
1
29
0
4
Order By: Relevance
“…The results showed that higher levels of parental acceptance/involvement, psychological autonomy granting, and strictness/supervision promoted higher EC in adolescents. These findings provide additional evidence of the importance of parenting in the development of EC in adolescents, consistent with prior studies (Stacey et al, 2016;Huang et al, 2017). In contrast to parenting, MAOA T941G polymorphism exerted no main effect.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that higher levels of parental acceptance/involvement, psychological autonomy granting, and strictness/supervision promoted higher EC in adolescents. These findings provide additional evidence of the importance of parenting in the development of EC in adolescents, consistent with prior studies (Stacey et al, 2016;Huang et al, 2017). In contrast to parenting, MAOA T941G polymorphism exerted no main effect.…”
Section: Discussionsupporting
confidence: 90%
“…These five Chinese parenting constructs were shown to not overlap with and were independent of the authoritative and authoritarian constructs identified in North American research [14]. Chinese mothers reported using more Chinese parenting than their U.S. and U.K. counterparts [14,33]; whereas the Chinese immigrant mothers in the U.S. and the U.K. reported similar level in the Chinese-specific parenting to their non-immigrant counterpart in Taiwan [34]. These findings demonstrated that these Chinese parenting practices are still prevalent in Chinese populations, including Chinese immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Parenting behaviors may have different cultural meanings in specific cultural contexts (Bornstein, Cote, & Venuti, ; Chao & Tseng, ). The roles of different parenting behaviors on children's outcomes may vary in different cultural contexts (Huang et al, ). Therefore, it is worth examining whether the roles of parenting behaviors on children's effortful control and math engagement may vary between the Chinese contexts and other cultural contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Although effortful control has its temperamental basis (Rothbart, Ahadi, Hershey, & Fisher, ), it does not suggest that parental behaviors play insignificant roles in children's effortful control. On the contrary, many studies have shown that parental behaviors were related to effortful control (Huang, Cheah, Lamb, & Zhou, ; Karreman, Van Tuijl, Van Aken, & Deković, ; Stormshak, Fosco, & Dishion, ). Specifically, it is argued that parental warmth may promote the development of children's effortful control by establishing positive parent–child relationships and providing good models of managing emotions and behaviors (Eisenberg, Smith, & Spinrad, ; Mun, Dishion, Tein, & Otten, ).…”
Section: The Present Studymentioning
confidence: 96%